2020
DOI: 10.1007/s11356-020-07898-y
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and molecular damage in Nile Tilapia (Oreochromis niloticus) after exposure to microplastics

Abstract: Recently, research on the biological effects of microplastics (MPs) has grown exponentially. However, effects of MPs on freshwater fishes and the mechanisms of the biological effects of MPs were limited. So, the purpose of the current study was to clarify the effects of microplastics on oxidative stress response, DNA fragmentation, and proteinogram of the early juvenile stage of Nile Tilapia (Oreochromis niloticus). The fishes were assigned into four groups: one control, three MPs-exposed groups as 1 mg/L of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(48 citation statements)
references
References 49 publications
7
30
0
Order By: Relevance
“…On the other hand, MT exposure was found not to alter CAT activity in zebrafish embryo (Rivero‐Wendt et al., 2016). Significant increase in plasma SOD and CAT activities, as observed in the present study, was reported in O. niloticus exposed to microplastics (Hamed et al., 2020). All four plant extract‐fortified diets lowered SOD values compared with control indicating their antioxidant and tissue protective potential.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, MT exposure was found not to alter CAT activity in zebrafish embryo (Rivero‐Wendt et al., 2016). Significant increase in plasma SOD and CAT activities, as observed in the present study, was reported in O. niloticus exposed to microplastics (Hamed et al., 2020). All four plant extract‐fortified diets lowered SOD values compared with control indicating their antioxidant and tissue protective potential.…”
Section: Discussionsupporting
confidence: 86%
“…For example, Yirong et al ( 2020 ) found that di (2-ethylhexyl) phthalate can induce apoptosis by stimulating an oxidative burst of neutrophils in carp ( Cyprinus carpio ). This apoptosis was explained by Walpitagama et al ( 2019 ), who supported the assumptions of reactive oxygen species (ROS)–prompted apoptosis demonstrated in our previous study (Hamed et al, 2020 ). In addition, polystyrene upregulated the expression levels of pro-apoptotic proteins, which are strictly linked to the commencement of cell apoptosis (Xu et al, 2019 ; Yirong et al, 2020 ).…”
Section: Discussionsupporting
confidence: 79%
“…Strunjak-Perovic et al ( 2009 ) reported that the nuclear anomalies may result from gene mutations in the nuclear lamina of the nucleus. Moreover, da Costa Araújo et al ( 2020a ) found that the genotoxicity of polyethylene MPs on erythrocytes was indirectly induced by the formation of free radicals that interfere with DNA integrity, and our previous study linking oxidative stress in tilapia with exposure to MPs (Hamed et al, 2020 ) reinforces this conclusion. On the contrary, no significant differences between PVC and Mater-Bi micro-debris–exposed groups and the control group were found in Dreissena polymorpha Mn (Magni et al, 2020 ).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…There was no oxidative stress and histological changes, however, induced behavioral abnormalities such as hyperactive swimming in the fish (Chen et al, 2020). On contrary, microplastics caused the overproduction of reactive oxygen species and alterations in the antioxidants parameters resulting in oxidative stress and DNA damage in Nile tilapia Oreochromis niloticus (Hamed et al, 2020). Polyvinyl microplastics when exposed through diet induced oxidative stress and hepatic damage in Clarias gariepinus (Iheanacho and Odo 2020a), and caused variations in hematology, antioxidant enzymes, lipid peroxidation, and acetylcholinesterase activity in African catfish Clarias gariepinus (Iheanacho and Odo, 2020b).…”
Section: In Fishesmentioning
confidence: 94%